Analisis Pertumbuhan Penduduk Terhadap Ketersediaan Fasilitas Sosial Ekonomi Di Kecamatan Pedan Kabupaten Klaten Tahun 2009 Dan 2013 - Kumalasanti, Sabrina, Drs. Priyono, M.Si, Drs. Dahroni, M.Si (2016)
This research is done in Pedan, Klaten with title "Analysis on Population Growth toward Social Economic Facility at Pedan, Klaten in 2009 and 2013". The purpose of this research is (1) to analysis the population growth in Pedan 2009 and 2013, (2) to analysis the factor that in influence the population growth in Pedan 2009 and 2013, (3) to analysis the influence population growth toward social economic facility in Pedan. The method that is used in this research in seconder data analysis that is get from office certain instance. That data consist of physical characteristic and non physical characteristic with comparison 2009 and 2013. The data analysis that is used is descriptive statistic analysis by using frequency and data statistical analysis tabulation. The analysis is doing by scoring or give score 1 until 3 for variables and to analyses factors that influence population growth by using formula CBR (Crude Birth Rate), CDR (Crude Death Rate), and Mn (Migration Neto). Whereas to find the correlation levels population growth with social economic facility using SPSS program with double linier regress formula. This research shows that population growth in the research area in 2009 and 2013 are include in low category with 0,18% presented. The decreasing of number population is caused by several factors influence level of population growth. The most influenced factor in population growth in research area is migration. It is because the number of migration is increased from 2009 with -38,3 until 2013 with 23,34, so in this research area level of population growth is low. In 2009 the calculation of correlation between population growth and education facility is R (0,417), the correlation between population growth and healthy facility is R (0,010), the correlation between population growth and economic facility is R (0,151). In 2013 the correlation between population growth and education facility is R (0,350), the correlation between population growth and healthy facility is R (0,079), the correlation between population growth and economic facility is R (0,202).